Parabacteroides timonensis sp. nov., identified in human stool. (December 2016) - Bilen, Melhem; Cadoret, Frederic; Daoud, Ziad; Fournier, Pierre-Edouard; Raoult, Didier
Abstract: We report the main characteristics of Parabacteroides timonensis sp. nov. strain Marseille-P3236 T (CSURP3236) that was isolated from a stool sample of a healthy 39 year-old pygmy male.